2022
DOI: 10.1111/apa.16423
|View full text |Cite
|
Sign up to set email alerts
|

Sodium supply from administered blood products was associated with severe intraventricular haemorrhage in extremely preterm infants

Abstract: Extremely preterm (EPT) infants frequently experience intraventricular haemorrhage (IVH) mainly occurring within the first 72 h after birth. 1,2 The incidence of IVH is inversely related to gestational age (GA) and birth weight (BW), and very immature preterm infants are more likely to experience the higher grades of IVH occurring earlier after birth. [2][3][4] While mild IVH (grades 1 and 2) has been shown to increase the risk of neurodevelopmental impairment to a lesser extent, severe IVH (grade 3 or peri-ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Sodium restriction was associated with a decreased incidence of hypernatraemia and bronchopulmonary dysplasia, and the authors concluded that sodium intake during the first 3–5 days of life should be restricted 28 . In a recent retrospective case–control study of 140 extremely preterm (GA < 27 week) infants by Späth et al., 31 a higher early sodium supply until postnatal day 2 was associated with an increased risk of severe intraventricular haemorrhage. A similar association was found in our data of VLBW infants: a higher sodium intake during the first two days of life was associated with an increased risk of IVH even in the absence of hypernatraemia.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium restriction was associated with a decreased incidence of hypernatraemia and bronchopulmonary dysplasia, and the authors concluded that sodium intake during the first 3–5 days of life should be restricted 28 . In a recent retrospective case–control study of 140 extremely preterm (GA < 27 week) infants by Späth et al., 31 a higher early sodium supply until postnatal day 2 was associated with an increased risk of severe intraventricular haemorrhage. A similar association was found in our data of VLBW infants: a higher sodium intake during the first two days of life was associated with an increased risk of IVH even in the absence of hypernatraemia.…”
Section: Discussionmentioning
confidence: 99%